2017
DOI: 10.3390/catal7110344
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Doped TiO2 Supported on HY Zeolite for Solar Photocatalytic Treatment of Dye Pollutants

Abstract: Zeolite-supported TiO 2 and Fe-doped TiO 2 /zeolite photocatalysts were synthesized, aiming at improving the adsorption properties of the microporous support towards polluting dyes and the photocatalytic performance of TiO 2 in the treatment of the adsorbed organics. The TiO 2 /HY zeolite catalyst exhibited the best performance in the photocatalytic degradation of methylene blue, MB, over 10 wt% TiO 2 /HY under UV light at 254 nm. The addition of Fe species in the synthesis mixture led to Fe-TiO 2 /HY catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 69 publications
1
25
0
Order By: Relevance
“…Therefore, the synthesis of efficient and environmentally friendly photocatalysts has attracted ever-increasing attention [9,10]. TiO 2 − and ZnO−based semiconductor materials are the most widely used photocatalysts in recent decades [11,12]. However, the main drawback for these materials is the fast recombination of electrons and hole pairs generated by irradiation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the synthesis of efficient and environmentally friendly photocatalysts has attracted ever-increasing attention [9,10]. TiO 2 − and ZnO−based semiconductor materials are the most widely used photocatalysts in recent decades [11,12]. However, the main drawback for these materials is the fast recombination of electrons and hole pairs generated by irradiation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Foura et al performed photocatalysis tests for 3-15 wt.% TiO 2 -loaded HY zeolite [67] in order to establish the influence of the amount of TiO 2 over degradation of MB under UV irradiation (Fig. 13).…”
Section: Removal Of Pollutant From Wastewaters Using Nanophotocatalystsmentioning
confidence: 99%
“…Results revealed that the HY zeolite has a very high influence on the degradation rate. TiO 2 particles at the surface of HY zeolite enhance the electron transfer from the semiconductor to the HY zeolite, and consequently, the zeolite prevents the electron-hole recombination [67,68]. The presence of the zeolite phase improves the photodegradation efficiency through synergistic factors such as high-specific surface area, adsorption capacities, and its ability to keep TiO 2 as a dispersed phase.…”
Section: Removal Of Pollutant From Wastewaters Using Nanophotocatalystsmentioning
confidence: 99%
“…Photocatalysis efficiency of TiO 2 -coated geopolymer for MB [21] Photocatalytic degradation of MB over TiO 2 and TiO 2 /zeolite under UV irradiation[67] …”
mentioning
confidence: 99%